Numerical study on the effect of four-lobe swirl generator and its transition parts on thermal performance enhancement and fluid flow - Diabis, Farag A.; Abu Talib, Abd Rahim; Mazlan, Norkhairunnisa; Supeni, Eris Elianddy (Semarak Ilmu Publishing, 2025)
Improving heat transfer in the field of thermal application is the targeted outcome of many researchers. The flow within smooth channels could not be mixed properly. Therefore, swirl flow techniques are taken into consideration because of their capability to promote the heat exchanger’s thermal efficiency by changing the flow's direction and creating a fluctuating flow between the channel's wall and core. The primary challenge that researchers frequently encounter with swirl flow techniques is the increased pressure loss. One of the most notable recent advancements is the lobed swirl generator, which achieves substantial swirl intensity with manageable pressure loss. Consequently, this study aims to explore and gain a deeper understanding of the thermal characteristics of the lobed swirl generator under various performance parameters. Consequently, the impact of a four-lobed swirl generator under a different twisted angle of (90 ≤ θ ≤ 450) and its transition part at essential parameters of transition multipliers (0.25 ≤ n ≤ 0.75) and variable helix (0.5 ≤ t ≤ 1.5) have been examined. The working fluid is water at the Reynolds number varies from 30,000 to 55,000 is conducted. The applicable shear-stress transport (SST) k-ω model has been adopted to model the turbulence swirling flow. According to the obtained results, the lobed swirl generator at (θ =360) and beta transition of (n = 0.5 mm) and (t =1 mm), the heat transfer and pressure loss increase compared with plain tube by 28.78 % and 17.35 %, respectively. By reducing the transition multipliers value to (n = 0.25 mm), a slight increase in heat transfer and pressure loss in the percentage by 40.32 % and 17.89 %, respectively are observed. The outcome demonstrated that lobed swirls could generate a centrifugal force under different conditions, which is the main significant character behind the heat transfer improvement.